Multiplicity-dependent inclusive J/[psi] production at forward rapidity in pp collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Menzel, Marius; Nath, Abhishek; et al. (Journal of high energy physics, 2025)
This paper presents a study of the inclusive forward J/ψ yield as a function of forward charged-particle multiplicity in pp collisions at √s = 13 TeV using data collected by the ALICE experiment at the CERN LHC. The results are presented in terms of relative J/ψ yields and relative charged-particle multiplicities with respect to these quantities obtained in inelastic collisions having at least one charged particle in the pseudorapidity range |η| < 1. The J/ψ mesons are reconstructed via their decay into μ+μ− pairs in the forward rapidity region (2.5 < y < 4). The relative multiplicity is estimated in the forward pseudorapidity range which overlaps with the J/ψ rapidity region. The results show a steeper-than-linear increase of the J/ψ yields versus the multiplicity. They are compared with previous measurements and theoretical model calculations.
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grunwald, M.W. Menzel, A. Nath, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, B. Windelband, A. Yuncu, F. Zanone, B. Zhang [und sehr viele weitere Personen]
Veröffentlicht: 23. Juli 2025
Gesehen am 08.01.2026
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol